PENINGKATAN KUALITAS PELAYANAN PUBLIK : KONSEP, INDIKATORINDIKATOR SERTA MODEL PENGUKURANNYA - Warsono, Hardi (Jurnal Desentralisasi, 2012)
The paradigm of public service reform direct public services quality improvement efforts on strengthening civil society, good governance, which looks at strengthening of the market mechanism and the greater community role in the formulation and implementation of public service policies. This is in line with the spirit of public service law that gives considerable space in the community's participation. Therefore, improving the quality indicators should also be reflected in the charge. Until now the government to assess the quality of public services by giving trophies to the two levels of service, ie, on a macro scale by giving Citra Bhakti Abdi Negara known by the acronym CBAN, and at the micro scale by awarding trophies Citra Pelayanan Prima (CPP). Macro associated with the assessment of the district / city governments in the provision of services to the community, while the micro is an assessment on service delivery in the unit of service providers.